LOFAR Observations of Substructure Within a Traveling Ionospheric Disturbance at Mid‐Latitude - Gareth Dorrian; Richard Fallows; Alan Wood; David R. Themens; Ben Boyde; Andrzej Krankowski; Mario Bisi; Bartosz Dąbrowski; Christian Vocks (Space Weather)
Abstract The large scale morphology and finer sub‐structure within a slowly propagating traveling ionospheric disturbance (TID) are studied using wide band trans‐ionospheric radio observations with the LOw Frequency ARray (LOFAR; van Haarlem et al., 2013, https://doi.org/10.1051/0004-6361/201220873). The observations were made under geomagnetically quiet conditions, between 0400 and 0800 on 7 January 2019, over the UK. In combination with ionograms and Global Navigation Satellite System Total Electron Content anomaly data we estimate the TID velocity to ∼60 ms−1, in a North‐westerly direction. Clearly defined substructures with oscillation periods of ∼300 s were identified within the TID, corresponding to scale sizes of 20 km. At the geometries and observing wavelengths involved, the Fresnel scale is between 3 and 4 km, hence these substructures contribute significant refractive scattering to the received LOFAR signal. The refractive scattering is strongly coherent across the LOFAR bandwidth used here (25–64 MHz). The size of these structures distinguishes them from previously identified ionospheric scintillation with LOFAR in Fallows et al. (2020), https://doi.org/10.1051/swsc/2020010, where the scale sizes of the plasma structure varied from ∼500 m to 5 km.